Club of Rome study: Limited prospects - Wolfgang Michalski (Intereconomics, 1972)
No other scientific publication in recent months has caused more of a stir and stimulated discussion than the Forrester-Meadows Study of the Massachusetts Institute of Technology (MIT) on behalf of the Club of Rome. In the following article the pessimistic assessment of the outlook for mankind in the MIT study is subjected to a critical examination.
Keywords: 330; Economic Growth